2012
DOI: 10.1007/s13197-012-0846-1
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of lead (Leucaena leucocephala) seed as affected by extraction solvent, prior dechlorophyllisation and drying methods

Abstract: Extracts of brown lead (Leucaena leucocephala) seed prepared using different extraction solvents were determined for antioxidative activities using different assays. The highest yield (3.4-4.0%) was obtained when water was used as an extraction solvent, compared with all ethanolic extracts used (1.2-2.0 %) (P<0.05). Much lower chlorophyll content was found in the water extract. When hot water was used, the resulting extract contained lower total phenolic and mimosine contents (P<0.05). In general, 60-80 % etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
76
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(88 citation statements)
references
References 47 publications
8
76
2
Order By: Relevance
“…The result was confirmed by FRAP method showing the reducing power activity of dried extract at 428.54 ±15.32 mM FeII equivalent/g. This result showed higher scavenging activity comparing to previous study 16 that observing the activity in seed extract 17,18 , suggested leave extract might provide greater scavenging activity compared with the seed part. The effects of L. leucocephala on HUVCs metabolites were shown in Figure 1 to 4, despite on each category.…”
Section: Conclusion and Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…The result was confirmed by FRAP method showing the reducing power activity of dried extract at 428.54 ±15.32 mM FeII equivalent/g. This result showed higher scavenging activity comparing to previous study 16 that observing the activity in seed extract 17,18 , suggested leave extract might provide greater scavenging activity compared with the seed part. The effects of L. leucocephala on HUVCs metabolites were shown in Figure 1 to 4, despite on each category.…”
Section: Conclusion and Discussioncontrasting
confidence: 53%
“…Total phenolic and flavonoid contents was determined, and the result showed 51.04 ± 0.91 mgGAE/g and 0.13 ± 0.01 mg of catechin/g content in dry leave extract, respectively. Likewise, other studies that found phenolic at 3.21 mg GAE/g, 33 37.38 ± 0.49 mg GAE/g, 17 78.8 g GAE/100g extract, 18 258.4±7.45 mg GAE/g, 16 7.51 to 12.06 mg GAE/g, 34 and flavonoid contents at 159.61±12.79 mg QE/g (Quercetin equivalent), 16 2.80 to 3.59 mg QE/g 34 depended on parts of plant collection and solution extracted. This compon ents suggest antioxidant activities of L. leucocephala, as confirmed in Table 1.…”
Section: Conclusion and Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Ethanol was reported to be an effective solvent for chlorophyll extraction (Sartory & Grobbelaar 1984). Benjakul, Kittiphattanabawon, Sumpavapol, and Maqsood (2014) reported that phenolic compounds and mimosine from lead seed could be effectively released when the water was used as the extraction medium, while lower amounts of chlorophyll were extracted. In general, a green colored extract might be an obstacle for further application.…”
Section: Total Chlorophyll Content (Tcc) and Colormentioning
confidence: 99%
“…Compared with other plants, the antioxidant property of Leucaena or other Mimosae has been investigated sporadically. Benjakul et al (2014) reported the antioxidant activities in Leucaena seeds and observed that the antioxidative activities were dependent on extracting solvents. The antioxidant activities in Mimosa pudica were also investigated (Genest et al 2008;Parmar et al 2015), but how much mimosine contributed to the antioxidant property in Leucaena and M. pudica has not been studied.…”
Section: Introductionmentioning
confidence: 99%